Influence Difference Workplace Stretching Exercise With Kinesiotapping Against Complaints Musculoskeletal Disorders On Unloading Labor At Makassar City Port - Nurhikmawaty Hasbiah; Andi Rahmaniar Suciani P; Andi Siti Irfah F; Aco Tang (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to determine the effect of workplace stretching exercise with kinesiotapping on reducing Musculoskeletal Disorders complaints in loading and unloading workers at Makassar City Port. This study is a quasi-experimental study with the dependent treatment variable in the form of workplace stretching exercise with Kinesiotapping, while the dependent variable is complaints of Musculoskeletal Disorders, the intervention is given 2 times a week for 2 months. The research design is a quasi experiment with a pretest-post test two group design. The research population is loading and unloading workers at the port of Makassar city. The number of samples is 20 people who are divided into 2 groups, namely the Kinesiotaping group and the workplace exercise group of 10 people each. This study uses VAS to measure Musculoskeletal Disorders pain before and after workplace stretching exercise treatment for treatment group I, and kinesiotapping for treatment group II. giving Workplace Stretching Exercise can reduce pain significantly with a value of <0.05 from 4.53 to 3.60 (scale 0-10). This shows that H0 is rejected, meaning that there is an effect of Workplace Stretching Exercise on the complaints of Musculoskeletal Disorders. Kinesiotapping can significantly reduce pain with a value of <0.05 from 4.73 to 3.93 (scale 0-10). This shows that H0 is rejected, meaning that there is an effect of kinesiotapping on the complaints of Musculoskeletal Disorders.